(untitled) (Medico Legal Update, 2020)
Bacterin can be divided into dead bacterin and live bacterin. Dead bacterin is a virulent strains which have a good immunogenicity .the aim of this study to know competitive between two bacterin E.coli and P.aeruginosa in different concentrations .The rabbits were used as model for this study and the rabbits were divided into six groups each groups composed 5 rabbits , After immunized programs .the blood were collected . The sera were separated and used to determine TNF-? ,IL-2 and IL-10 by enzyme linked immunosorbent assay .the results appeared .The results appeared different count of bacteria increased (54.09, 68.33)TNF-? compared with control(42.55) . the concentrations of Il-2 were increased with increased dose of E .coli (16.90, 20.29)also the same occurred with P .aeruginosa (in P aeruginosa alone was15.14 while combined with E.coli 15.56 and15.38 ,the results appeared the means of IL-2 concentrations were higher, Interleukin 10 were showed its mean was increased in same concentrations of bacterin but decreased in different count . The present findings seems to be novel since combined bacterins have the potential for use as an autogenous bacterins in therapy for cases of complicated multi-drug resistant infections like that of urinary tract.